Study of desert dust events over the southwestern Iberian Peninsula in year 2000: two case studies - V. E. Cachorro; R. Vergaz; R. Vergaz; A. M. de Frutos; J. M. Vilaplana; D. Henriques; N. Laulainen; C. Toledano (Annales Geophysicae, 2006)
Strong desert dust events occurring in 2000 over the southwestern Atlantic coast of the Iberian Peninsula are detected and evaluated by means of the TOMS Aerosol Index (A.I.) at three different sites, Funchal (Madeira Island, Portugal), Lisboa (Portugal) and El Arenosillo (Huelva, Spain). At the El Arenosillo station, measurements from an AERONET Cimel sunphotometer allow a more precise retrieval of the spectral AOD and the derived alpha Ångström coefficient. After using different threshold values of these parameters, we conclude that it is difficult to establish reliable and robust criteria for an automatic estimation of the number of dust episodes and the total number of dusty days per year. As a result, additional information, such as airmass trajectories, were used to improve the estimation, from which reasonable results were obtained (although some manual editting was still needed). A detailed characterization of two selected desert dust episodes, a strong event in winter and another of less intensity in summer, was carried out using AOD derived from Brewer spectrometer measurements. Size distribution parameters and radiative properties, such as arefractive index and the aerosol single scattering albedo derived from Cimel data, were analyzed in detail for one of these two case studies. Although specific to this dust episode, the retrieved range of values of these parameters clearly reflect the characteristics of desert aerosols. Back-trajectory analysis, synoptic weather maps and satellite images were also considered together, as supporting data to assess the aerosol desert characterization in this region of study.